Single incision fasciotomy to treat compartment syndrome in diabetic foot: A case report. - Rampal, Sanjiv; Syukur, Mohamad Hasaan; Bajuri, Mohammad Yazid (2012)
Compartment syndrome of the foot is a rare but well-documented condition caused by increased myofascial compartment pressure. Outcomes following surgical intervention for this condition can be improved by careful pre-operative planning and gentle handling of the soft tissue involved during the procedure. The authors report an unusual case of compartment syndrome in a person with diabetes who presented with foot pain significantly out of proportion to the associated injury. Following diagnosis of acute compartment syndrome, surgical treatment was undertaken.